Clinical Impact of Melphalan Pharmacokinetics on Transplantation Outcomes in Children Undergoing Hematopoietic Stem Cell Transplantation. (December 2022) - Maemura, Ryo; Wakamatsu, Manabu; Matsumoto, Kana; Sakaguchi, Hirotoshi; Yoshida, Nao; Hama, Asahito; Yoshida, Taro; Miwata, Shunsuke; Kitazawa, Hironobu; Narita, Kotaro; Kataoka, Shinsuke; Ichikawa, Daisuke; et al.
Melphalan is widely used for hematopoietic stem cell transplantation (HSCT) conditioning. However, the relationship between its pharmacokinetic (PK) and transplantation outcomes in children has not been thoroughly investigated. We prospectively analyzed the relationship between melphalan area under the curve (AUC) and transplantation outcome and examined the development of a predictive model for melphalan clearance in children. This study included 43 children aged 0 to 19 years who underwent HSCT following a melphalan-based conditioning regimen from 2017 to 2021. In univariable analysis, high-melphalan AUC resulted in a significantly lower cumulative incidence of acute graft-versus-host disease and a higher cumulative incidence of thrombotic microangiopathy, although no significant difference was observed in survival. Regression analysis of a randomly selected derivation cohort ( n = 21) revealed the following covariate PK model: predicted melphalan clearance (mL/min) = 6.47 × 24-h urinary creatinine excretion rate (CER, g/day) × 24-h creatinine clearance rate (CCR, mL/min) + 92.8. In the validation cohort ( n = 22), the measured melphalan clearance values were significantly correlated with those calculated based on the prediction equation ( R 2 = 0.663). These results indicate that melphalan exposure may be optimized by adjusting the melphalan dose according to CER and CCR.